THE PERCEIVED VALUE OF DESIGN FOR NEW PRODUCTS AT MICRO AND SMALL COMPANIES - Grieco Mazzini Junior, Edu; Benitez Nara, Elpidio Oscar; Mählmann Kipper, Liane; Weber Reuter, Julia; Pereira Burin, Heloisa (Revista Latino-Americana de Inovação e Engenharia de Produção, 2019)
The research aims to identify and promote improvements in the planning and development processes of new products with the insertion of the design. The study was developed in three micro and small furniture companies, which are located in the city of Santa Maria-RS. This market segment was chosen because it has changes in the execution of its productive processes and by the constant search of new products in order to meet the requirements of its customers. Based on the evaluations of the final consumers and the control of the information provided by the managers of the planning and production sectors, it was sought to qualify the products based on the design. A multiple case study was used in order to identify the main differences between visions in the generation of new products. Based on this, the quality evaluation matrix, Quality Function Deployment (QFD) was used to identify and quantify procedures that have a greater impact between the planning and execution of new tailored furniture. It was possible to detect difficulties in the insertion of the design in the Furniture Industries. It is necessary to overcome some obstacles to change the company’s culture regarding the management of new products